2000
DOI: 10.1007/s001010070113
|View full text |Cite
|
Sign up to set email alerts
|

Bedeutung der Perfusion des Gastrointestinaltrakts im Schock

Abstract: The splanchnic perfusion is reduced early in the course of any shock. The mucosa of the gut suffers most as it experiences a high oxygen demand even in the steady state. The specific arrangement of the micro vessels within the villus of the mucosa exposes the tip of the villus at the highest risk for ischemia, particularly in low flow states. As a consequence the integrity of the mucosal layer is compromised and dysfunction of the mucosal barrier may allow bacteria and toxins to translocate from the gut lumen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…16,17 Endothelial cells play a key role in sepsis pathogenesis and microcirculatory dysfunction, [18][19][20] and an endothelial cell-specific molecule-1 (endocan, a 50-kDa dermatan sulfate proteoglycan) is expressed on endothelial cells and is acknowledged as a suitable marker of endothelial dysfunction. 21,22 Furthermore, Frey and Kesel 23 reported that splanchnic perfusion decreases early in sepsis. In our previous study, dexmedetomidine attenuated intestinal microcirculation alteration in a rat model of surgical stress and pain stimulation.…”
mentioning
confidence: 99%
“…16,17 Endothelial cells play a key role in sepsis pathogenesis and microcirculatory dysfunction, [18][19][20] and an endothelial cell-specific molecule-1 (endocan, a 50-kDa dermatan sulfate proteoglycan) is expressed on endothelial cells and is acknowledged as a suitable marker of endothelial dysfunction. 21,22 Furthermore, Frey and Kesel 23 reported that splanchnic perfusion decreases early in sepsis. In our previous study, dexmedetomidine attenuated intestinal microcirculation alteration in a rat model of surgical stress and pain stimulation.…”
mentioning
confidence: 99%